2014
DOI: 10.1097/01.asw.0000443898.56886.66
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrosurgery System (Versajet) with and without Hydrogen Peroxide Solutions for the Debridement of Subacute and Chronic Wounds

Abstract: Encouraging results were obtained with the use of the hydrosurgery system prepared with hydrogen peroxide for infected subacute and chronic wounds. This method decreased hospital stay and bleeding, thus providing better contact of the skin graft with the wound bed, allowing early rehabilitation. The findings of the authors' study need to be substantiated in large-scale randomized controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…At the level of observational studies, [18][19][20][21][22][23][24][25] the quality of the evidence is low to moderate and the conclusions of some of them are not sufficiently supported by the results report. 23 Effectiveness of debridement is mainly supported by the evolution of healing and graft success, and not by the biopsy study.…”
Section: Resultsmentioning
confidence: 92%
“…At the level of observational studies, [18][19][20][21][22][23][24][25] the quality of the evidence is low to moderate and the conclusions of some of them are not sufficiently supported by the results report. 23 Effectiveness of debridement is mainly supported by the evolution of healing and graft success, and not by the biopsy study.…”
Section: Resultsmentioning
confidence: 92%
“…Mohammadi et al in a randomized clinical trial of chronic colonized burn wounds showed that 2% hydrogen peroxide wound cleansing significantly improved skin graft take rates 41. Another trial by Irkoren demonstrated that hydrosurgery with hydrogen peroxide was superior to controls without hydrogen peroxide for infected wounds, resulting in shorter hospital stay and enhanced graft viability 42.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…It has been shown that the use of each of them alone exerts a bacteriostatic effect, but their combination has a bactericidal effect 17–19 . In addition to the fact that hydrogen peroxide has micro debridement properties by producing O 2 when acted upon by catalase enzyme 20 . These unique properties encouraged their combined use in orthopedic surgery and plastic surgery 21,22 .…”
Section: Discussionmentioning
confidence: 99%